Children’s and adolescents’ engagement with music and the potential for (digital) empowerment processes: A text-mining-supported scoping review - Smolarczyk, Kathrin; Birnbaum, Lisa; Christ, Alexander; Kröner, Stephan (Psychology of Music, 2024)
Extracurricular and out-of-school engagement with music is often associated with positive effects for musical goals while also holding potential for developmental and empowerment processes. The COVID-19 pandemic has highlighted the importance and the potential of digital technologies for facilitating musical engagement. The emergence of digitally transformed musicking has added complexity to the already multifaceted and complex field of research on non-formal musical engagement. Thus, the aims of this text-mining-supported scoping review are (1) to map and describe the underlying research topics in the field of children’s and adolescents’ musical engagement, (2) to explore potential for empowerment processes, and (3) to identify the extent to which digital aspects emerge. Based on N = 624 articles, a topic-modeling procedure yielded k = 10 topics covering cognitive, emotional and attitudinal, youth cultural and digital aspects. Among these, one predominantly digital topic comprised studies on the production and consumption of music. Implications for the potential for empowerment can be drawn from studies that focus on youth cultural aspects, such as hip-hop culture and digital aspects. Limitations and implications for further research are discussed, including how to transfer these findings and how new technologies can further enhance music-making and creation.
CRIS-Team Scopus Importer:2024-05-10
Keywords: empowerment; music; non formal education; scoping review; text-mining